2005
DOI: 10.1097/01.wnr.0000186601.50996.f7
|View full text |Cite
|
Sign up to set email alerts
|

Differential brain activation according to chronic social reward frustration

Abstract: Neural correlates of reward frustration are increasingly studied in humans. In line with prediction error theory, omission of an expected reward is associated with relative decreases of cerebral activation in dopaminergic brain areas. We investigated whether a history of chronic work-related reward frustration influences this reward-dependent activation pattern by means of functional magnetic resonance imaging. Solving arithmetic tasks was followed by either monetary reward or omission of reward. Hyperactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 21 publications
3
34
0
3
Order By: Relevance
“…For example, adults with high trait aggression exhibit decreased activation of dorsal ACC in response to frustration (Pawliczek et al, 2013) while children (ages 6–9) with clinically significant irritability exhibit similar decreases in activation in a more rostral region of dorsal ACC (Perlman et al, 2015). Alternatively, decreased responding in a similar region of the ACC has been observed in a non-clinical sample of adults with high susceptibility to frustration (Siegrist et al, 2005). Finally, in a magnetoencephalography (MEG) study, a similar, but older, sample (ages 8–17) to that presented here (ages 5–9.9), showed increased activity of rostral ACC, along with higher ratings of agitation and sadness, in response to negative feedback, compared to healthy controls (Rich et al, 2011).…”
mentioning
confidence: 76%
“…For example, adults with high trait aggression exhibit decreased activation of dorsal ACC in response to frustration (Pawliczek et al, 2013) while children (ages 6–9) with clinically significant irritability exhibit similar decreases in activation in a more rostral region of dorsal ACC (Perlman et al, 2015). Alternatively, decreased responding in a similar region of the ACC has been observed in a non-clinical sample of adults with high susceptibility to frustration (Siegrist et al, 2005). Finally, in a magnetoencephalography (MEG) study, a similar, but older, sample (ages 8–17) to that presented here (ages 5–9.9), showed increased activity of rostral ACC, along with higher ratings of agitation and sadness, in response to negative feedback, compared to healthy controls (Rich et al, 2011).…”
mentioning
confidence: 76%
“…So far, the mechanisms underlying these associations have not been fully explored, although recent experimental evidence on reward frustration and unfairness suggests that, in addition to reduced motivation and commitment, an enhanced activation occurs in those parts of the brain reward system that trigger recurrent stress reactions in the organism [35,36]. Other plausible mechanisms include alterations in autonomic functioning, inflammatory, or immune responses [37,38], for example, impaired host resistance increasing the likelihood of common cold [39]; sleep disturbances [40,41]; and unfavourable life style changes that contribute to morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility to reward frustration was measured by scores on the scales assessing effort-reward imbalance at work (76). The findings suggested that exposure to chronic frustration after effort compromises the adaptive responsiveness of parts of the cortical system to received or omitted rewards.…”
Section: Suggestions For Future Research and Conclusionmentioning
confidence: 99%